2000
DOI: 10.1017/s0033291799002500
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue rating scales: an empirical comparison

Abstract: Findings revealed that both scales are appropriate and useful measures of fatigue-related symptomatology and disability within a general population of individuals with varying levels of fatigue. However, the Fatigue Severity Scale appears to represent a more accurate and comprehensive measure of fatigue-related severity, symptomatology, and functional disability for individuals with CFS-like symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 12 publications
0
65
0
4
Order By: Relevance
“…However, fatigue was observed at baseline, as indicated by a fatigue severity scale score of .36 [35], and a nonsignificant fall was observed after 3 months of ASV therapy, bringing this score back into the normal range. Fatigue has not been evaluated in comparable intervention trials.…”
Section: Discussionmentioning
confidence: 95%
“…However, fatigue was observed at baseline, as indicated by a fatigue severity scale score of .36 [35], and a nonsignificant fall was observed after 3 months of ASV therapy, bringing this score back into the normal range. Fatigue has not been evaluated in comparable intervention trials.…”
Section: Discussionmentioning
confidence: 95%
“…Although the expected association was not defined, a head-to-head comparison of the ChalderFS (index and domain scores) and FSS following completion by a large patient group (n = 166) reported very low correlations between the two measures, suggesting that they measure different aspects of fatigue [100]. The FSS had stronger correlations with variables reflecting CFS severity and the generic Short-Form 36-item Health Survey (SF-36) [101], leading the authors to suggest that the FSS provides a more comprehensive reflection of fatigue-related severity, symptomology and functional disability than the ChFS.…”
Section: Measurement Propertiesmentioning
confidence: 91%
“…In addition, the Fatigue Severity Scale (Krupp et al, 1989) was normed on a sample of individuals with MS, SLE, and healthy controls. A study by Taylor, Jason and Torres (2000) found that, within a CFS-like group, the Fatigue Severity Scale was associated with severity ratings for the eight Fukuda et al (1994) CFS symptoms. (Friedberg, 1996), a quantitative measure of depression severity was used.…”
Section: Methodsmentioning
confidence: 99%